Evaluation of the strain identity between isolates from caries lesions and root canals in early childhood caries cases - Nováková, Dana; Svec, Pavel; Kukletová, Martina; Záčková, Lenka; Sedláček, Ivo (Folia microbiologica, 2013)
Early childhood caries (ECC) has become a serious medical problem worldwide in the last decade. Bacterial microflora of the dental plaque and oral cavity is considered an important factor in the formation and progression of dental caries. The aim of this study was strain typing and comparison of bacterial isolates retrieved from caries lesions and root canal contents of the same teeth. In total, 18 pairs of presumptive streptococci and lactobacilli retrieved from dental caries and root canals isolated from ECC-affected children, were selected on the basis of biotyping results and rep-PCR fingerprinting with (GTG)5 primer. Strain typing was further done using the RiboPrinter microbial characterization system (DuPont Qualicon). The automated ribotyping determined 14 pairs of the strains (77.8 %) to be identical. The results obtained confirmed that identical bacterial strains colonized both the decayed dental surface and the necrotic content of the dental pulp cavity during the cariogenesis. Our finding supports the assumption that bacteria could penetrate through the damaged dental surface to the inner parts of the teeth.
Keywords: zubní kaz; Female; Streptococcus; dítě; předškolní dítě; polymerázová řetězová reakce; Polymerase Chain Reaction; ženské pohlaví; DNA Fingerprinting; lidé; Dental Caries; DNA fingerprinting; Male; kavita zubní dřeně; Child, Preschool; Lactococcus; Bacterial Typing Techniques; ribotypizace; techniky typizace bakterií; Child; mužské pohlaví; Ribotyping; Dental Pulp Cavity; Humans